Penerapan Manajemen Bandwith Jaringan Internet Sekolah Menggunakan Metode Peer Connection Queue (Studi Kasus: SMP Sandrem) - Santosa, Sugeng Iman; Juardi, Didi; Heryana, Nono (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2024)
The aim of this study is to implement equitable bandwidth management on the internet network at SMP Sandrem using the Peer Connection Queue (PCQ) method during activities such as downloading, uploading, and browsing. Additionally, this research aims to configure bandwidth management using the PCQ method on both wired and wireless media. The research methodology used is the Network Development Life Cycle (NDLC), which includes stages such as analysis, design, simulation, prototype, implementation, monitoring, and management. The results of the study show that the implementation of bandwidth management using the PCQ method successfully provides fair and equitable allocation to each user. Through the use of simple queues, network configuration, monitoring, and management become easier. Testing on 2 devices showed an allocation of approximately 10 Mbps, while with 3 devices, the allocation was around 6-7 Mbps. This bandwidth management approach offers flexibility and scalability without rigid maximum bandwidth limitations. In conclusion, the implementation of bandwidth management using the PCQ method at SMP Sandrem has had a positive impact on effective bandwidth allocation and network quality improvement in the school. Recommendations include regular monitoring, evaluation, and adjustment of the implemented configurations to maintain optimal network performance and meet user requirements.